(untitled) (Lebenswelt. Aesthetics and philosophy of experience., 2014)
This essay aims to discuss a potential conflict between two intuitions about material objects: a ’pluralist’ one, according to which every object belongs (or may belong) to more than one kind, and a ’reductionist’ one, according to which there is only one fundamental type of things, i.e., material things. The former view threatens to translate a merely subjective matter of fact into an ontological fact, while the latter naturally leads to an outdated form of physicalism. What then? How to satisfy both the request for a precise ontology and the need to make sense of the richness of our experience of things? The paper reconstructs the general structure of the issue, and explores two ways of solving it via the formulation of an intermediate view.